2014
DOI: 10.1088/0022-3727/59/21/6659
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose enhancement at tissue-tungsten interfaces in HDR brachytherapy

Abstract: HDR BrachyView is a novel in-body dosimetric imaging system for real-time monitoring and verification of the source position in high dose rate (HDR) prostate brachytherapy treatment. It is based on a high-resolution pixelated detector array with a semi-cylindrical multi-pinhole tungsten collimator and is designed to fit inside a compact rectal probe, and is able to resolve the 3D position of the source with a maximum error of 1.5 mm. This paper presents an evaluation of the additional dose that will be deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Increased dose to the patient due to backscatter is possible. However, prior studies attempting to quantify backscatter exposure with Iridium-192, a higher energy source than Iodine-125 have revealed that the backscatter dose is essentially negligible at > 1 mm [31]. For our shield, it is practically difficult to measure the radiation exposure on the patient's side of the shield due to the radiation emitted directly from the sources inside the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Increased dose to the patient due to backscatter is possible. However, prior studies attempting to quantify backscatter exposure with Iridium-192, a higher energy source than Iodine-125 have revealed that the backscatter dose is essentially negligible at > 1 mm [31]. For our shield, it is practically difficult to measure the radiation exposure on the patient's side of the shield due to the radiation emitted directly from the sources inside the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Ir HDR brachytherapy source. The core consists of pure iridium with a uniform distribution of 192 Ir, surrounded by a steel shell (Borg et al, 1999a;Han et al, 2014).…”
Section: Compton Scatter Correctionmentioning
confidence: 99%